Driving GRI-Based Sustainability Reporting through Board Characteristics and Skills in Indonesia’s Non-Financial Sector - Wina; Oscar, Yosia; Lestari, Henny Setyo; Leon, Farah Margaretha (Syntax Corporation, 2025)
This study examines the influence of board characteristics and skills on sustainability reporting (SR) in Indonesia’s non-financial sector, focusing on companies listed on the Indonesia Stock Exchange (IDX) between 2021 and 2023. Using the Generalized Least Squares method, the study investigates how board size, independence, gender diversity, and specific skills impact the quality of sustainability reports, assessed using the Global Reporting Initiative (GRI) standards. Results show that board size negatively affects SR, indicating that smaller boards with the right composition are more effective in enhancing sustainability disclosures. Board independence was found to have no significant impact, suggesting that merely meeting regulatory requirements may undermine its intended purpose. Board gender diversity, however, positively influenced SR, as women on boards tend to be more engaged with sustainability and stakeholders. Additionally, board-specific skills were found to have no significant effect on SR. Among control variables, firm profitability and age positively influenced SR, while leverage negatively affected it, indicating that highly leveraged firms are motivated to enhance sustainability reporting to gain stakeholder trust. This study provides valuable insights into corporate governance and sustainability reporting, offering recommendations for future research and policy improvements in Indonesia’s business ecosystem.